Pemberdayaan Potensi Tenaga Kesehatan Jejaring FK UMI dalam Upaya Promosi Kesehatan dan Screening Stunting di Kab.Luwu - Utami, Dian Fahmi; Royani, Ida; Syahril, Erlin; Latief, Shofiyah; Natasha, Ratih; Andi Mappaware, Nasrudin; Andi Pangnguriseng, Utomo (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Stunting is a physical growth disoder characterized by a decrease in growth rate and is the impact of nutritional imbalance with measurements based on the body length index for age or height for age with a z-score of less than -2SD . UNICEF data in 2013 about 1 in 4 children under five are stunted. Basic Health Research (Rsikesdas) 2013, there were 37.2% of children under five who were stunted with an increasing prevalence compared to the 2010 Riskesdas results, which was 35.6%. The target of this research is to reduce the incidence of stunting by empowering the potential of Faculty of Medicine of Universitas Muslim Indonesia network health workers in their various capacities as lecturers and health practitioners (Specialists, General Practitioners, Internship Doctors and Professional Doctor Program Students) in an effort to promote health and stunting screening in the district. Luwu together with the Luwu Regency Government, Stikes KJP and IBI for the Luwu Regency area. In this service, as many as 74.2% of health workers understand, recognize and prevent stunting. As many as 87.7% had known the function of medical personnel in disseminating the importance of screening and 72.5% had known their role in controlling and guarding the community in carrying out routine examinations. New supporting data was obtained regarding the nutritional status of toddlers in Luwu Regency, South Sulawesi Province which can be used as further research in reducing the incidence of stunting.